$\sum_{n=0}^{\infty} \frac{x^{2 n}}{(2 n) !}=$
【答案】 $\frac{1}{2} e^x+\frac{1}{2} e^{-x}$

【解析】 令 $s(x)=\sum_{n=0}^{\infty} \frac{x^{2 n}}{(2 n) !}$, 则 $s^{\prime}(x)=\sum_{n=1}^{\infty} \frac{x^{2 n-1}}{(2 n-1) !}, s^{\prime \prime}(x)=\sum_{n=1}^{\infty} \frac{x^{2 n-2}}{(2 n-2) !}=\sum_{n=0}^{\infty} \frac{x^{2 n}}{(2 n) !}=s(x)$. 即有 $s^{\prime \prime}(x)-s(x)=0$, 解得 $s(x)=C_1 e^x+C_2 e^{-x}$.
又由 $s(0)=1, s^{\prime}(0)=0$ 有 $C_1+C_2=1, C_1-C_2=0$ 解得 $C_1=C_2=\frac{1}{2}$. 故 $s(x)=\frac{1}{2} e^x+\frac{1}{2} e^{-x}$.
系统推荐